Remington : essentials of pharmaceutics - Felton, Linda A. (Philadelphia : Philadelphia College of Pharmacy ; London : Pharmaceutical Press, 2013)
A complete guide to the theory and application of pharmaceutics.
Information resources in pharmacy and the pharmaceutical sciences / Robin H. Bogner and Sharon Giovenale -- Analysis of medicinals / Raymond D. Skwierczynski -- Quality assurance and control / John H. Parker and John E. Enders -- Stability of pharmaceutical products / Allan D. Bokser and Patrick B. O'Donnell -- Bioavailability and bioequivalence / Steven B. Johnson -- Dissolution / Vijai Kumar and Praveen Hiremath -- Modern-day drug discovery and development / Rick G. Schnatz -- The new drug approval process / Linda A. Felton and Dennis W. Raisch -- Metrology and pharmaceutical calculations / Roger L. Schnaare and Shelly J. Prince -- Statistics / Sanford Bolton and Richard Hirsch -- Molecular structure, properties and states of matter / Thomas Rades, Keith C. Gordon, and Kirsten Graeser -- Thermodynamics / Timothy S. Wiedmann -- Solutions and phase equilibria / Pardeep K. Gupta -- Separation methods / Lloyd V. Allen -- Ionic solutions and electolytic equilibria / Barbara R. Conway -- Tonicity, osmoticity, osmolality, osmolarity / Andrew Ingham and Cathy Y. Poon -- Chemical kinetics / Rodney J. Wigent -- Complex formation / Thorsteinn Loftssori and Marcus E. Brewster -- Interfacial phenomena / Paul M. Bummer and Yvonne Perrie -- Colloidal dispersions / Bill Bowman, Clyde M. Ofner III, and Yvonne Perrie -- Coarse dispersions / James Swarbrick, Joseph T. Rubino, and Orapin P. Rubino -- Rheology / Lawrence H. Block -- Powders / Y-Bo Wang and Robert O. Williams -- Solutions, emulsions, suspensions, and extracts / Michael M. Crowley -- Sterilization processes and sterility assurance / James Agalloco, William G. Lindboem, Jr., and Russell E. Madsen -- Parenteral preparations / Michael J. Akers -- Pharmaceutical compounding - USP <797> sterile preparations / Catherine Cone, Linda A. Felton, and Amy Bachyrycz -- Ophthalmic preparations / Masood Chowhan, John C. Lang, and Paul Missel -- Medicated topicals / Lawrence H. Block -- Oral solid dosage forms / Ahmed Adel Sakr and Fars K. Alanazi -- Coating of pharmaceutical dosage forms / Stuart C. Porter -- Oral modified-release drug delivery systems / Ali R. Rajabi-Siahboomi, Manish S. Rane, and Linda A. Felton -- Aerosols / John J. Sciarra and Christopher J. Sciarra -- Biotechnology and drugs / Ara H. DerMarderosian and Zhiyu Li -- Pharmaceutical packaging / C. Jeanne Taborsky and Kathleen Deiss -- Pharmaceutical excipients / William J. Reilly, Jr. -- Basic pharmacokinetics and pharmacodynamics / Raymond E. Galinsky and Craig K. Svensson -- Drug action and effect / Donald N. Franz -- Drug absorption, distribution, metabolism and excretion / Michael R. Franklin -- Pharmacokinetics/pharmacodynamics in drug development / George L. Drusano.
"This books is adapted from contributions published in Remington : The Science and Practice of Pharmacy 22nd edition"--T.p. verso.
pharmacy bookfair2015
Includes bibliographical references and index.
Keywords: Drugs -- Dosage forms; Drugs -- Handbooks, manuals, etc; Pharmacology -- Handbooks, manuals, etc; Pharmacy -- Practice -- Handbooks, manuals, etc; Dosage Forms